(untitled) (Research, Society and Development, 2021)
The nutritional and physiological condition of the cow during pregnancy has been associated with fetal formation and future progeny performance. The objective of the work was to evaluate the effects of the history of the pregnant cow on the progeny performance. 343 Charolais and Nellore beef cows were used, divided according to reproductive history: pregnant cows that repeated pregnancy (P); empty cows that have impregnated (V). The data were collected during 5 years in the experimental herd. V cows had a higher body condition score (BCS) (2.83 vs 3.05 points) and body weight at the end of the reproductive season (462.72 vs 478.82 kg), in addition to a lower BCS at calving (2.58 vs 2.64 points) and greater weight loss during pregnancy (-35.17 vs -13.34 kg) compared to P cows. The weight adjusted at 205 days of age was higher in the progeny of P cows (140.54 vs 139.35 kg), with no effects at 365 and 540 days (P>0.05). The performance at 7 months of age was higher in the progeny of P cows (0.517 vs 0.502 kg/day), while the progeny of V cows was superior at 12 and 18 months of age, with values ​​respectively of 0.558 vs 0.397 and 0.397 vs 0.351 kg/day. Calves of P cows showed higher Kleiber value at 7 months, while the progeny of V cows was more efficient at 12 months. The reproductive history of the cow influences the performance of the progeny, where empty cows produce calves with greater productive potential in adulthood.